2015
DOI: 10.1016/j.bbamem.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of binding events on a thermostabilized human A2A receptor embedded in a lipid bilayer by surface plasmon resonance

Abstract: Membrane proteins (MPs) are prevalent drug discovery targets involved in many cell processes. Despite their high potential as drug targets, the study of MPs has been hindered by limitations in expression, purification and stabilization in order to acquire thermodynamic and kinetic parameters of small molecules binding. These bottlenecks are grounded on the mandatory use of detergents to isolate and extract MPs from the cell plasma membrane and the coexistence of multiple conformations, which reflects biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 34 publications
1
73
2
Order By: Relevance
“…Specifically, the k on values we obtain for micelle-solubilized A 2A R are within ~10 fold of those for FITC-APEC 22 and 5–10 fold of those determined from ZM 241,385 and NECA using [ 3 H]-ZM 241,385 4 for wild-type A 2A R in membrane preparations. The k on values for ZM 241,385 agonist-selected, truncated variants (thermostabilized A 2A -Star2 and rant21) found also using exponential fits were ~50–500 fold higher than we determined in this study 31, 32 . Interestingly, our k off estimate and those of the other reports vary only by ~0.5–15 fold, indicating much less variability in k off for ZM 241,285 relative to k on .…”
Section: Resultscontrasting
confidence: 50%
“…Specifically, the k on values we obtain for micelle-solubilized A 2A R are within ~10 fold of those for FITC-APEC 22 and 5–10 fold of those determined from ZM 241,385 and NECA using [ 3 H]-ZM 241,385 4 for wild-type A 2A R in membrane preparations. The k on values for ZM 241,385 agonist-selected, truncated variants (thermostabilized A 2A -Star2 and rant21) found also using exponential fits were ~50–500 fold higher than we determined in this study 31, 32 . Interestingly, our k off estimate and those of the other reports vary only by ~0.5–15 fold, indicating much less variability in k off for ZM 241,285 relative to k on .…”
Section: Resultscontrasting
confidence: 50%
“…194 Possible partitioning of the ligand into the lipid bilayer of Nanodiscs was accounted for by placing empty Nanodiscs in the reference channel. Results of this work confirmed that label-free monitoring of small molecule binding kinetics of the membrane protein in Nanodiscs could be performed using SPR, suggesting a new approach to the measurement of the influence of agonistic or antagonistic ligands on the binding of G proteins or β-arrestin to the extracellular or intracellular sides of the bilayer.…”
Section: Application Of Nanodiscs In Functional Studies Of Membranmentioning
confidence: 99%
“…Both studies demonstrate the powerful potential of this approach. The influence of lipid composition upon assay performance was recently investigated in a comparative study of the adenosine A 2A receptor employing four different reconstitution approaches (Bocquet et al, 2015). When the receptor was reconstituted in lipid nanodiscs, protein stability was enhanced and the kinetic data obtained were more similar to native receptors compared with those solubilized in detergents.…”
Section: Surface Plasmon Resonance Analysismentioning
confidence: 99%